Analysis on Internal Corrosion in a Natural Gas Pipeline - WAN Qiong, LI Guang - ze (Cailiao Baohu)
Since a gas pipeline was put into operation in October 2006, there had been five pipeline leakage incidents in this section of the pipeline, and all of the leakage points were at the bottom of the pipeline. By experimenting with failed pipes, such as wall thickness test, physical and chemical test, analysis of corrosion products and anti - corrosive coating test, the internal corrosion was analyzed, combined with construction files. Results showed that the pipeline was damaged due to carbon dioxide corrosion and bacterial corrosion. By draining residual water in the pipeline and improving the cleanliness of natural gas, the risk of internal corrosion of the pipeline could be reduced effectively.